If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5z-3z=5
We move all terms to the left:
5z-3z-(5)=0
We add all the numbers together, and all the variables
2z-5=0
We move all terms containing z to the left, all other terms to the right
2z=5
z=5/2
z=2+1/2
| 18÷–18×(–6×12+–14)=n | | -y=-2y-1 | | `25^{2}=125^{x+1}` | | 4x-3=-5x21 | | d=14(10) | | 6•x-5=13 | | 2^3x+1=42 | | -6a+(-2a)=-24 | | 4d+(-10d)=-36 | | −x(−3−4x)(−4−4x)=0 | | -4f+8f=16 | | -8m+(-3m)=-55 | | 5g+(-15g)=40 | | -3k+(-3k)=-18 | | -6g+8g=10 | | 5m+(-10m)=-15 | | 2y+8y=-60 | | (-k+3/5)(1/3k+5/3)=0 | | 48x=100+x^2 | | X*y=306 | | (5n+3)=4 | | 0.7x=4200 | | 5+x=17−2+7 | | c-11=-18 | | 10x-1x=360 | | 2/9x+36=8/x+4-7/9 | | -1/4(16b-20)=7b-16 | | 5-2(3x+1)=-21 | | 6-x/2=20 | | 52.5+-0.5y=70+-2y | | 5(5-6)=4(y-7) | | 5b+23=8-23 |